A Biblical Study of Yahweh: The Forgotten Divine Name and Its Implications for Indonesian Christians in Their Use of God's Name - Iskandar, Jahja (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2025)
The name Yahweh, the proper and covenantal name of the God of Israel, carries deep historical, theological, and devotional significance. However, its usage has diminished or been forgotten among many believers, including Christians in Indonesia. This study examines the biblical, historical, and linguistic factors contributing to the obscurity of Yahweh in contemporary Christian worship, especially in the Indonesian context. Drawing from texts such as Jeremiah 23:23–32, the research highlights the spiritual and doctrinal implications of neglecting God's revealed name. The findings emphasize that recovering the understanding and reverence for the name Yahweh is vital for fostering a deeper relationship with God and for enhancing theological clarity in the church. The study also suggests that Indonesian church leaders play a key role in reintroducing this biblical truth through teaching and liturgy, thereby strengthening the foundation of Christian identity and worship.